Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3855/jidc.5359
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between virulence factors and genotype of Candida spp. isolated from blood cultures

Abstract: NAC species were the most common causative agent for candidemia. Genotyping showed low transmission of C. albicans strains, but transmission of C. parapsilosis was high. In candidemia, several Candida virulence factors may be responsible at the same time. However, different genotypes of Candida strains showed different virulence activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
3
16
1
3
Order By: Relevance
“…Proteinase production aids host immune system evasion through the degradation of albumin, α‐macroglobulin and other human proteins . Membrane phospholipid hydrolysis by phospholipase leads to cell lysis and causes tissue damage . In this study, virulence attributes production was more intense in C. albicans than in the other studied species.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Proteinase production aids host immune system evasion through the degradation of albumin, α‐macroglobulin and other human proteins . Membrane phospholipid hydrolysis by phospholipase leads to cell lysis and causes tissue damage . In this study, virulence attributes production was more intense in C. albicans than in the other studied species.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, a study reported strong proteinase and phospholipase activities in C. albicans isolates; only one C. parapsilosis isolate was identified as a proteinase producer, and no phospholipase or proteinase activity was detected in the C. glabrata isolates . Furthermore, a study found higher phospholipase and proteinase activities in C. albicans isolates than in NCA species . A Brazilian study observed haemolytic activity in C. albicans , C. glabrata , C. tropicalis and C. parapsilosis .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, only an enzyme called Sapt1p was purified from culture supernatants and biochemically characterized (Zaugg et al, 2001). C. tropicalis is still able to produce satisfactory amounts of phospholipase, which catalyzes the hydrolysis of phospholipids in host cells membranes (Silva et al, 2012; Mutlu Sariguzel et al, 2015). Hemolysins are another group of enzymes involved in Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…After incubation, a 10 μL suspension of each sample was deposited on plates containing the egg yolk agar medium (1% peptone, 3% glucose, 5% NaCl, 0.0006% CaCl2, 2% agar and 10% egg yolk). Plates were then incubated at 35°C for 48 h. The precipitation zone (Pz) value was calculated as follows [25]: Pz = . The Pz value was then used to evaluate the phospholipase activity and it was defined as follows [16]: Pz = 1, negative phospholipase activity; Pz = 0.90–0.99, very low phospholipase activity; Pz = 0.80–0.89, low phospholipase activity; Pz = 0.70–0.79, high phospholipase activity; Pz ≤ 0.69, very high phospholipase activity.…”
Section: Methodsmentioning
confidence: 99%